Field of Dreams: Imagining Development and Un-Development at a Gas Field in Sylhet - Katy Gardner; Zahir Ahmed; Mohammad Masud Rana; Fatema Bashar (South Asia Multidisciplinary Academic Journal)
In this article we analyse the discourses which surrounded a Chevron operated gas field and programme of ‘Community Engagement’ in Sylhet over 2008-11. All draw upon ideas of development or its absence, and reference dreams, as well as nightmares of the future. On the one hand are Chevron’s narratives, which conjure up an appealing picture of community development, entrepreneurship and ‘empowerment’, relying upon idioms of sustainability and ‘helping people to help themselves’. On the other are the narratives of people living in the villages surrounding the installation. Whilst for them, dreams of unnoyon (development) involve the provision of local services, access to gas and the creation of jobs, their accounts evolve around the tropes of environmental destruction and disastrous rupture: a dystopian anti-development.